Determinant Intention to Adopt AI-Powered Robo Advisors - Zidane Ramadhan; Umi Widyastuti; Meta Bara Berutu (PENG: Jurnal Ekonomi dan Manajemen, 2026)
Fintech in Indonesia are increasingly becoming popular, but penetration in the society is still minimal especially in investment context. This paper examines the possible drivers toward intention to adopt of AI-powered robo advisor through a modified VAM model with attitude toward using and age as moderating factors. Survey data were collected from Generation Z and millennial investors and analyzed using SEM-PLS. Our analysis shows that potential financial benefits gained from AI-powered robo advisors drives positive attitude and intention to adopt, while risk associated with AI-powered robo advisor demotivate users to adopt it. External social influences also positively impact the adoption process, demonstrating the importance of social validation in Indonesia's communal culture. Attitude toward using shows a significant performance in explaining intention to adopt AI-powered robo advisor. Moderation analysis shows that age strengthens the influence of perceived financial benefits on intention to adopt (stronger in millennials),and weakens the influence of social influence (stronger in Gen Z). These results provide theoretical and practical contributions in designing age-based marketing strategies and improving financial literacy. Future research is recommended to reach a wider demographic and conduct longitudinal studies as this technology develops